Pilah-timbang-setor mandiri: Inovasi Bank-Sampah Permata-Cimanggis atasi keterbatasan lahan pilah sampah di rumah tangga: Indonesia - Nurhayati, Entin; Putra, Johan Satria (UII, 2024)
In the neighborhood of Permata Cimanggis Housing, household waste has become a troublesome problem due to the unavailability of land for waste disposal. The increasing volume of waste has led to efforts to reduce final waste through waste bank activities. This activity succeeded in reducing the final waste by 20 to 40%. However, another issue emerged at the household level, as there was insufficient space to temporarily store the waste before depositing it in the waste bank. This lack of space has reduced the number of waste bank customers, especially during the pandemic, because the presence of waste is considered a nuisance to the residents of the house who are at home every day. As a result, the amount of final waste has increased again. This has made it difficult for the RT/RW to manage the waste. Efforts need to be made to reduce waste and encourage people to become active waste bank customers. Using an action research approach, the author and team tried to solve the problem. In the first cycle, observations and interviews were conducted with several waste bank customers. From the observations and interviews, the idea to create a simple station to collect waste at the household level was initiated. The second step was to present the idea in a discussion forum with the community. From the discussion process with the waste bank manager, several waste bank members, and ‘RW’ administrators, a new system in the waste bank was finally agreed upon, namely the self-deposit system. In this system, ‘RW’ provides a place to store the waste. The manager provides equipment that allows customers to deposit waste independently without having to wait for the waste bank to open. In this way, it is hoped that the stored waste will not be piled up at home, thus the problem of limited area at home is solved.